Tinjauan Hukum Tentang Pencatatan Perkawinan Di Kantor Urusan Agama - Andi Besse Simpur; Lauddin Marsyuni; Dwi Handayani (Qawanin Jurnal Ilmu Hukum, 2020)
This study aims to determine and analyze the records of marriages in the religious affairs office of Bantimurung sub-district, as well as to identify and analyze the causes of not registering marriages in the religious affairs office of Bantimurung district.This study uses empirical research methods, sampling is obtained through interviews and direct research with employees and staff of the religious affairs office as well as literature studies related to research, the number of samples is two people, the research location is in the religious affairs office in Bantimurung district, data collection techniques are Librarian studies and field studies, in this case interviews, and the data obtained are processed by qualitative analysis with a deductive approach. The results of this study indicate that: 1.) the registration of marriages at the Office of Religious Affairs, Bantimurung District, can be said to have not been fully implemented because from the research results there were still unregistered marriages. There are at least about 13% marriages that are not recorded each year. The phenomenon that usually occurs is usually because the husband commits polygamy without the permission of the wife and it is done not in front of the KUA officer, 2. an understanding of the benefits of registering marriage and second marriage and so on after widowing and widowers. Research recommendations for the Office of Religious Affairs and the Government need to work together in order to further optimize its duties in educating the public, through counselling and disseminating information regarding the importance of registering marriages in the religious affairs office. Abstrak:Penelitian ini bertujuan untuk mengetahui dan menganalisis tercatatnya perkawinan di kantor urusan agama kecamatan bantimurung,serta untuk mengetahui dan menganalisis faktor penyebab tidak dicatatnya perkawinan di kantor urusan agama kecamatan bantimurung. Penelitian ini menggunakan metode penelitian empiris, penarikan sampel diperoleh melalui wawancara dan penelitian secara langsung dengan pegawai dan staff kantor urusan agama serta studi kepustakaan yang berhubungan dengan penelitian, jumlah sampel sebanyak dua orang, lokasi penelitian di kantor urusan agama kecamatan bantimurung,tehnik pengumpulan data yaitu studi kepustaaan dan studi lapangan dalam hal ini wawancara, dan data yang diperoleh diolah dengan analisis kualitatif dengan pendekatan deduktif. Hasil penelitian ini menunjukkan bahwa: 1.) pencatatan perkawinan di Kantor Urusan Agama Kecamatan Bantimurung dapat dikatakan belum dilaksanakan sepenuhnya karena dari hasil penelitian masih terdapat perkawinan yang tidak tercatat. Terdapat sedikitnya sekitar 13% perkawinan yang tidak tercatat setiap tahun nya. Fenomena yang biasa terjadi biasanya karena suami melakukan poligami tanpa seizin istri dan dilakukan tidak didepan petugas KUA,2.) faktor penyebab tidak tercatatnya perkawinan di kantor urusan agama kecamatan bantimurung yaitu pertama, karena tidak terpenuhi syarat administratif,hamil diluar nikah,keinginan poligami,kurangnya pemahaman terhadap manfaat pencatatan perkawinan dan pernikahan kedua dan seterusnya setelah menjanda dan menduda